Perlindungan Hukum Terhadap Konsumen yang Menerima Alat Pembayaran yang Tidak Sah dalam Transaksi Jual beli Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. - Ariestya, Fiena; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Law no. 8 of 1999 on Consumer Protection has given the force of law that the consumer has an equal footing with businesses, as well as to raise consumer awareness of their rights against businesses that acted arbitrarily and also raise awareness of liability businesses. The problems posed in the writing of this paper is how consumer protection laws against the change does not comply with consumer rights Act No. 8 of 1999 on Consumer Protection. With regard to the right of consumers to accept the change, when the money more than necessary is used to pay at the modern minimarket, sometimes events happen that should not, in which the officers who serve've not return the remaining money should be received by the consumer. This course can be categorized as an action that makes consumers feel uncomfortable. The research method is that the sociological law research and data collection is done by searching for information based on the questionnaires, interviews and review of literature, which it aims to determine the legal protection of consumers that the change does not comply with consumer rights Act Law No. 8 of 1999 on Consumer Protection. The conclusion of this study is consumers are feel aggrieved in material and immaterial because their rights are not given as they should and deserve to get legal protection.Keywords: Cash back, Consumer Rights, modern minimarket